2018
DOI: 10.5604/01.3001.0010.7799
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Evaluation of Rubber Composites Using Terahertz Time Domain Spectroscopy

Abstract: In recent years, with the progress of science, more and more detection methods are being used in various fields. However, the nondestructive testing of nonmetallic materials still needs further study. In this paper, an analysis of the time domain characteristics of rubber materials using terahertz detection technology was carried out, obtaining different defect rubber material spectral characteristics as well as imaging results and data. The results show that the THz spectrum imaging technique can detect the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Finally, the THz‐TDS system was used to visualise the thickness distribution of the rubber sample. The delamination defects of the sample were successfully detected by combining THz imaging of the internal defects of different bonding structures with spectroscopic testing and visual imaging of a three‐layer bonding structure [95, 96]. Previous studies also reported using terahertz technology to detect defects in simplified models of vehicle cable terminals.…”
Section: Online Monitoring and Defect Detection Methodsmentioning
confidence: 99%
“…Finally, the THz‐TDS system was used to visualise the thickness distribution of the rubber sample. The delamination defects of the sample were successfully detected by combining THz imaging of the internal defects of different bonding structures with spectroscopic testing and visual imaging of a three‐layer bonding structure [95, 96]. Previous studies also reported using terahertz technology to detect defects in simplified models of vehicle cable terminals.…”
Section: Online Monitoring and Defect Detection Methodsmentioning
confidence: 99%
“…As one of the three major polymer materials, rubber has high elasticity than metal, high mechanical strength and good bending resistance. Because of its unique properties, rubber is widely used in medical and health, power communication, civil engineering and other fields [22]. Glass fiber reinforced composites are widely used in the bearing and electromagnetic wave transmission structures of unmanned aerial vehicles due to their excellent strength-weight ratio, aerodynamic performance and microwave permeability [23].…”
Section: Imaging Samples Experimental Methods and Image Processing Sample Introduction And Experimental Setupmentioning
confidence: 99%
“…Although the D-S evidence theory has been a promising and popular approach for NDE data fusion especially in recent years, 22 the computation of the value of the mass functions remains largely an unsolved challenge (i.e., there is currently no unique solution to all applications). Quite a few strategies have been documented in the literature to determine this parameter, 97,98 but studies argue that the process to calculate the mass value should always be as objective as possible to guarantee the accurate representation of the different NDE data sources. 18 Additional issues include but are not limited to the exponential complexity of computations (in the general worst-case scenario) as well as the likelihood of obtaining counterintuitive results when fusing conflicting data.…”
Section: Dempster-shafer Evidence Theorymentioning
confidence: 99%